Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T19:14:07+01:00
A)2x+6=20
2x= 20-16
2x=14/:2
x=7

b)23+9y+50
9y= 50-23
9y= 27/:9
y= 3

c)8y-36=24
8y= 24+36
8y= 60/:8
y= 7,5

d)-4c-46=-2
-4c= -2+46
-4c= 44/: (-4)
c= -11

e)13+2x=3
2x= 3-13
2x=-10/:2
x=-5

f)-7=5x+1
-7-1=5x
-8=5x/:5
x= -1³/₅

g)7x-21=5x
7x-5x=21
2x=21/:2
x=10,5

h)6y-13=-52
6y= -52+13
6y= -39/:6
y= 6,5

i)4x-4=3
4x=3+4
4x= 7/:4
x= 1³/₄
1 5 1
2010-03-17T19:18:41+01:00
A)2x+6=20/-6
2x=14/:2
x=7

b)23+9y=50/-23
9y=27/:9
y=3

c)8y-36=24/+36
8y=60/:8
y=7,5

d)-4c-46=-2/+46
-4c=44/:(-4)
c=-11

e)13+2x=3/-13
2x=-10/:(-2)
x=5

f)-7=5x+1/-1
-8=5x/:5
x=1,6

g)7x-21=5x/-7x
-2x=-21/:(-2)
x=10,5

h)6y-13=-52/+13
6y=-39/:6
y=6,5

i)4x-4=3/+4
4x=7/:4
x=1,75

Pozdro :D
1 5 1
2010-03-17T19:18:52+01:00
A) 2x+6=20
2x=20-6
2x=14 | :2
x=7

b) 23+9y=50-23
9y=27 | :9
y=3

c) 8y-36=24
8y=24+36
8y=30 | :8
y=7,5

d) -4c - 46 = -2
-4c = -2 + 46
-4c = 44 | : (-4)
c = 11

e) 13+2x=3
2x=3-13
2x=-10 | :2
x= -5

f) -7=5x+1
-7-1=5x
5x = -8 | : 5
x = -8/5
x = -1 i 3/5

g) 7x - 21 = 5x
7x - 5x = 21
2x = 21 | : 2
x= 21/2
x = 10 i 1/2

h) 6y - 13 = -52
6y= -52+13
6y= -39 | :6
y = -39/6
y = 6,5

i) 4x - 4 = 3
4x = 3+4
4x = 7 | :4
x = 7/4
x = 1 i 3/4
1 5 1